2019
DOI: 10.3390/nu11051112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Relationship between Low Calcium Intake and High Blood Pressure

Abstract: There is increasing epidemiologic and animal evidence that a low calcium diet increases blood pressure. The aim of this review is to compile the information on the link between low calcium intake and blood pressure. Calcium intake may regulate blood pressure by modifying intracellular calcium in vascular smooth muscle cells and by varying vascular volume through the renin–angiotensin–aldosterone system. Low calcium intake produces a rise of parathyroid gland activity. The parathyroid hormone increases intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 114 publications
1
57
0
4
Order By: Relevance
“…This study found that dietary Ca intake was associated with reduced SBP and PP. This is consistent with other studies that examined dietary antioxidant intake and its relationship with BP [72][73][74][75][76]. However, in a doubleblinded, placebo-controlled clinical trial, the intake of Ca-rich diet reduced DBP but not SBP [26,77].…”
Section: Relationship Between Dietary Micronutrient Intake and Cardiosupporting
confidence: 90%
“…This study found that dietary Ca intake was associated with reduced SBP and PP. This is consistent with other studies that examined dietary antioxidant intake and its relationship with BP [72][73][74][75][76]. However, in a doubleblinded, placebo-controlled clinical trial, the intake of Ca-rich diet reduced DBP but not SBP [26,77].…”
Section: Relationship Between Dietary Micronutrient Intake and Cardiosupporting
confidence: 90%
“…The parathyroid gland secretes parathyroid hormone and the parathyroid factor. Both mediators increase cytosolic free Ca concentration, leading to the contraction of vascular smooth muscle tissue [ 31 ]. Therefore, Ca intake may affect smooth muscle function on utero-placental flow.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure is regulated by intracellular calcium in vascular smooth muscle cells, through vasoconstriction and variations of the vascular volume [51,52]. Low calcium intake seems to trigger both mechanisms, raising plasma parathyroid hormone (PTH) levels, that increase intracellular calcium directly or through calcitriol activation, and stimulating the renin–angiotensin–aldosterone signalling pathway that produces sodium and water reabsorption, thus increasing the vascular volume [42,52,53,54,55]. Parathyroidectomized rats in comparison with sham-operated rats did not show an increase in blood pressure after 10 weeks of a calcium-free diet [54].…”
Section: Calcium Intake and Effect On Blood Pressurementioning
confidence: 99%